Complex investigations of the critical n-amylic alcohol-nitromethane mixture with acousto-optic methods - Mikołaj ŁABOWSKI; Tomasz HORNOWSKI (Archives of Acoustics)
Acoustic properties of tho critical n-amylic alcohol-nitromethane mixture have been analysed in the ultra- and hypersonic range for two concentrations and at two temperatures. On the basis of obtained values of propagation velocities and acoustic wave absorption coefficients, fundamental physical, chemical and acoustic parameters have been determined, as well as the ratio of the total intensity of the central component to two MANDEJSZTAM-BRILLOUIN components for individual concentrations of the investigated mixture. Experimental results of investigations of absorption coefficients in a wide range of acoustic wave frequencies have been compared to the theories of FIXMAN and CZABAN. Also average life-times of concentration fluctuations in the n-amylio alcohol-nitromcthane mixture have been estimated with the application of experimental results. This was done not only in the direct nearness of the temperature of component separation, but at temperatures distant from it also according to the method given by M. J. SZACHPRANOW and P. K. CHABIBUŁŁAJEW, The method of determining the mean correlation radius of concentration fluctuations and the mean radius of intermolecular interactions on the basis of the intensity of dispersed light in terms of the angle is described and measurement results of these quantities in the investigated mixture in the direct nearness of the critical point are given. The kinetics of concentration fluctuations in the n-amylic alcohol-nitromethane mixture are analysed. With the application of the achieved mean concentration relaxation time, τ_α, correlation radius of concentration fluctuations, ξ, and the diffusion coefficient, D, the average length of concentration waves Λ_α in the mixture under investigation has been determined.